The prevalence of interstitial lung disease and bronchiectasis in rheumatoid arthritis: A systematic review and meta-analysis - Baekdal, Jonas Aggerholm; Janns, Laurits Kramer; Hansen, Erik Sören Halvard; Meteran, Howraman; Bendstrup, Elisabeth; Ulrik, Charlotte Suppli (Sarcoidosis, Vasculitis and Diffuse Lung Diseases, 2025)
Background and Aim: Rheumatoid arthritis (RA) is associated with an increased risk of interstitial lung disease (ILD) and bronchiectasis. Understanding the prevalence of these diseases is essential for timely diagnosis and management. Our aim was to estimate the prevalence of ILD and bronchiectasis in RA patients.Study Design and Methods: A systematic literature search was performed on PubMed, Embase, and Google Scholar to identify all studies performing HRCT in consecutive RA patients. Articles were screened by three independent authors in accordance with PRISMA guidelines. Random-effects meta-regression was performed to estimate the prevalence according to RA duration and C-reactive protein. Results: Twenty-four studies comprising 2,532 RA patients were included. The estimated prevalence of ILD at the time of RA diagnosis was 8.5% (95% CI: 4.4–12.5%), increasing by 3.0 percentage points (95% CI: 2.1–3.9%) per year after RA diagnosis (P